OPTIMALISASI PENGUNAAN AFFILIATE MARKETING TERHADAP BUSINESS TO BUSINESS (B2B) - Adiguna, Patria; Sasongko, Fajar; Nurhayati, Nurhayati; Firmansyah, Firmansyah; Fayruz, Muhammad (Universitas Islam Al-Ihya Kuningan, 2025)
The rapid development of information technology has significantly impacted various aspects of life, including the business sector. One major shift is the transition from conventional sales methods to digitalization, commonly known as e-commerce. The use of smartphones among students has positive effects in facilitating communication and work but also poses risks of addiction. To address this issue, one potential solution is Affiliate Marketing, which enables students to generate passive income while making their smartphone usage more productive. Affiliate Marketing is a digital marketing strategy that involves collaboration between individuals and companies or platforms to earn revenue through product promotion. This activity aims to enhance students' understanding of Affiliate Marketing through a structured training program. The methodology includes socialization, simulations, hands-on practice, discussions, and evaluation through questionnaires. The results indicate an increase in student knowledge from 11.56% to 91.92%, as well as the potential for additional income through Affiliate Marketing. The study concludes that Affiliate Marketing serves as an innovative approach to reducing smartphone addiction while enhancing student productivity.